Rubus alutaceus (Rosaceae), a new species for Colombia with agronomic potential - Brigitte Liliana Moreno–Medina; Fánor Casierra–Posada; Sofía Albesiano (Revista Brasileira de Fruticultura, 2020)
Abstract In Gachantivá, Colombia, Rubus alutaceus has been used for commercial purposes for more than one decade but so far with unknown taxonomic identity. For its identification, the anatomical and morphological characteristics of its flowers, fruits, leaves, stems, and seeds, as well as the physicochemical characteristics of its fruits such as color, equatorial and polar diameter, fresh weight, pH and total soluble solids (TSS), were studied. Qualitative and quantitative morphological parameters were evaluated, and longitudinal and transverse cuts were made for histological studies. The plants were found to have trifoliate and pentafoliate leaves; whitish–yellow subglobose polydrupes, fully mature fruits with 8.8°Brix TSS; elliptical, subglobose seeds with ruminated endocarps; anatomical calcium oxalate crystals in the form of druses and raphides in the leaves and branches; and abundant hairs, simple and glandular (colleters) addition to vascular tissue with a more or less continuous appearance. High value in TSS, positively influences fruit agribusiness and the presence of simple hair and colleters can reduce the attack of pests, these variables identify the new species and give it agronomic potential to strengthen its cultivation and marketing.